Decision tree model based prediction of the efficacy of acupuncture in methadone maintenance treatment - Dong, Yu; Fan, Baochao; Yan, Enliang; Chen, Rouhao; Wei, Xiaojing; Zhan, Jie; Zeng, Jingchun; Wen, Hao; Lu, Liming (Frontiers in Neurology, 2022)
Background Patients with MMT often face difficulties such as sleep disturbance, headaches, and difficulty in complete abstention from drugs. Research has shown that acupuncture can mitigate side effects while attenuating methadone dependence. It also has a synergistic and attenuated effect on MMT. Exploring the predictors of the efficacy of acupuncture intervention in MMT might help clinicians and patients promote acupuncture-assisted participation in MMT, and improve clinical treatment strategies. Objective To describe the effect of potential predictors on MMT after acupuncture intervention by building a decision-tree model of data from A Clinical Study of Acupuncture-assisted MMT. Design, setting, and participants In this randomized controlled trial, 135 patients with MMT underwent acupuncture at the Substance Dependence Department of Guangzhou Huiai Hospital in Guangzhou, Guangdong Province, China. Intervention 135 patients were 1:1 randomly assigned to either an acupuncture plus routine care group (acupuncture plus methadone) or a routine group (methadone only) for 6 weeks, and followed up for 10 weeks. Sex, age, education level, route of previous opioid use, years of opioid use, and MMT time were recorded before the trial. Outcome measurements and statistical analysis All analyses were based on the intention-to-treat (ITT) population. The two decision tree models used the change of methadone dosage and the VAS score for opioid desire as response variables respectively, and the evaluation criteria were positive effect (decreased by ≥20%) and no effect (decreased by＜20%, or increased). We generated the respective feature weights for the decision tree, and evaluated the model’s accuracy and performance by Precision-Recall. Results The overall accuracy of methadone reduction and psychological craving VAS scoring decision trees were 0.63 and 0.74, respectively. The Methadone Dosage Efficacy decision tree identified years of opioid use (Weight = 0.348), acupuncture (Weight = 0.346) and route of previous opioid use (Weight = 0.162) as key features. For VAS Score decision tree, acupuncture (Weight = 0.618), MMT time (Weight = 0.235) and age (Weight = 0.043) were the important features. Conclusion Exploratory decision tree analysis showed that acupuncture, years of opioid use, route of previous opioid use, MMT time, and age were key predictors of MMT treatment.